Upaya Guru Kelas dalam Meningkatkan Prestasi Belajar Fiqih Peserta Didik di MI Salafi Dukuhsembung - Kastinah; Kusuma Ningtyas Pramita Resya (La-Tahzan: Jurnal Pendidikan Islam, 2022)
This research is motivated by the teacher's position is very significant in education as a facilitator and guide, so that the teacher's efforts determine the success of the learning process. The purpose of this research is to find out and research scientifically and systematically about the efforts, obstacles and solutions made by class teachers to improve the fiqh learning achievement of students in Salafi Madrasah Ibtidaiyah. To find out the results in improving the achievement of fiqh subjects of students in Madrasah Ibtidaiyah Salafi Dukuhsembung Pangkah Tegal. This research based on the location of the data source is categorized as field research, and in terms of the nature of the data is included in qualitative research. Data collection methods using observation interviews and documentation. Data analysis was conducted starting from data reduction, data presentation, and drawing conclusions. Research results: 1) The efforts of class teachers in improving students' fiqh learning achievement are as follows: a) providing motivation to students, b) creating good conditions in the teaching and learning process, c) using learning methods that are in accordance with the situation and conditions of students, d) using interesting learning media in accordance with learning materials. 2) The inhibiting factors of the class teacher's efforts in improving the fiqh learning achievement of MI Salafi Dukuhsembung Pangkah Tegal students are a) There are students who have less ability, b) Limited supervision from the madrasah to supervise students. c) Lack of awareness of the students of the importance of learning. 3) The solution of the class teacher in improving the fiqh learning achievement of MI Salafi Dukuhsembung Pangkah Tegal students are: a) the school provides special guidance to students who are less capable. b) There is cooperation from parents and schools to provide supervision, with the hope that students will further improve their learning achievement, c) Raising awareness of students to like reading subject books rather than watching television.